The development of an instructional design model as a strategic enabler for sustainable competitive advantage. Part 2 - L. Le Roux; H. Oosthuizen (South African Journal of Business Management, 2010)
In a business environment of continuous change and in light of a defined need to fast track skills improvement in South Africa and Africa, training strategies and practices are under increasing pressure to develop a more productive and skilled workforce. Demands on training and the practices it employs increasingly focus on the alignment with strategic imperatives of organisations.This research presented an instructional design (ID) model positioned in the intersection between the positioning-based and resource-based theories and used a multi-disciplinary approach to extend the literature on ID models and offer measurable improvements in job-specific knowledge and productive behaviour as proxies for sustainable competitive advantage. The research confirmed the contribution of the ID model in this regard and described and substantiated the pivotal link between training and ID models and the application thereof in practice to aid organisations in the achievement and sustainability of competitive advantage. In this, the second article, the ID model will be subjected to empirical investigation and evaluated through the application thereof in a case organisation and a grounded conclusion provided. Hence, this article presents a brief overview of the first article, and focuses on the research methodology, research results, analysis and interpretation; conclusions and assessment of the research.This is the second in a series of two articles.
Keywords: 650